PERTIMBANGAN HAKIM DALAM GUGATAN SALAH PIHAK (ERROR IN PERSONA) PERKARA PERSELISIHAN HUBUNGAN INDUSTRIAL (Studi Putusan Nomor 353/ Pdt.Sus-PHI.G/2019/PN.JKT.PST): The Judge's Consideration In Error In Persona In Industrial Relations Disputes (Study of Decision Number 353/Pdt.Sus-PHI.G/2019/PN.JKT.PST) - Nadya Larasati Adinda; Andari Yurikosari (Reformasi Hukum Trisakti, 2025)
This research examines the legal issues between Hadi Yanto and PT Terang Jaya Lestari, specifically related to the error in persona exception in Case Decision Number 353/Pdt.Sus-PHI.G/2019/PN.JKT.PST. This dispute focuses on the validity of the party sued in the lawsuit filed by the plaintiff. The identification of the problem in this article; how the judge's consideration in resolving the case, and to explore the legal consequences arising from the decision of the judge's ruling and consideration. The research method uses normative juridical with analytical descriptive nature and is analyzed qualitatively. The research results and conclusions show that the lawsuit filed by the plaintiff is not in accordance with the applicable statutory provisions, especially related to errors in determining the party being sued, known as error in persona. In this case, the plaintiff made a mistake in suing an improper party, which resulted in the rejection of the lawsuit by the judge. The judge's consideration that the lawsuit cannot be accepted based on this party error shows the importance of clarity in the identification of parties in every lawsuit, especially in the context of resolving industrial relations disputes. This research is expected to contribute to the understanding of the application of legal principles in dispute resolution in the field of industrial relations.